2013
DOI: 10.1109/tap.2012.2214752
|View full text |Cite
|
Sign up to set email alerts
|

A Circularly-Polarized Array Antenna Using Linearly-Polarized Sub Grid Arrays for Highly-Integrated 60-GHz Radio

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…A microstrip patch antenna can be conventionally designed using the following equations given empirically by [16] as: Where h is the substrate thickness and W is the width of the patch. The effective length of the patch Leff now becomes: = + 2∆ Where, L is the patch length.…”
Section: Methodology 21 Mathematical Formulation Of Patch Antennamentioning
confidence: 99%
“…A microstrip patch antenna can be conventionally designed using the following equations given empirically by [16] as: Where h is the substrate thickness and W is the width of the patch. The effective length of the patch Leff now becomes: = + 2∆ Where, L is the patch length.…”
Section: Methodology 21 Mathematical Formulation Of Patch Antennamentioning
confidence: 99%
“…A broadband circularly polarized antenna having compact size is proposed in [1] and is designed with a loop feeding structure which will provide sequential phase, four driven patches and four parasitic patches. The axial ratio can be widened by adding all these patches.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the D-band frequency range 141 to 148 GHz is proposed for back-haul point-to-point relay stations and thus, several D-band Grid Array Antennas (GAA) have been developed and characterized for this purpose lately [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases Liquid Cristal Polymer (LCP) is used [1] and in some cases Low temperature Co-fired Ceramics (LTCC) [2][3][4][5][6]. A cost benchmark on these two antennas has shown that, in small volume production, counting volumes of 500 antennas, the two solutions are very similar in cost.…”
Section: Introductionmentioning
confidence: 99%